Adaptive Power Management Strategy for a Four-Mode Hybrid Electric Vehicle. (May 2017) - Guan, Jen-Chiun; Chen, Bo-Chiuan
Abstract: A conventional vehicle propelled with only the internal combustion engine (ICE) is not easy to enhance the fuel economy due to the wide range operation requirement of the powertrain. However, a hybrid electric vehicle (HEV) which consists of an ICE and one or multiple electric motors can effectively improve the efficiency of the powertrain. In this paper, we propose an adaptive power management strategy (PMS) based on the equivalent fuel consumption minimization strategy (ECMS) for a four-mode HEV. The four-mode HEV which consists of an ICE and two motors provides four modes of operation, including electric vehicle (EV) mode, range extended (RE) mode, hybrid mode, and engine mode. The adaptive PMS is designed for charge sustaining such that the state of charge (SOC) can be maintained at a certain value. A self-organizing fuzzy controller (SOFC) is employed to adaptively adjust the equivalence factor of electric energy consumption based on the SOC deviation and the change of SOC deviation. An instantaneous cost function which consists of the fuel consumption of ICE and the equivalent fuel consumption of the battery is minimized to obtain the optimum power distributions of the ICE and two motors. Simulation results show that the adaptive PMS can effectively improve the fuel economy for different driving cycles.